Empresário e dependência no pensamento político de Fernando Henrique Cardoso (1957-1967) - Laporta, Daniel Osterreicher (Universidade Federal de São Carlos, 2010)
This text aims to study the Fernando Henrique Cardoso s works focusing the author s ideas concerning the industrial society and the brazilian post 1930 s modernization. It is intended to make a short descriptive and theoretical examination about the academic carrer of this intelectual and to analyse part of his political thoughts, which is those of greater theoretical centrality and contribution for the development theories, both the cepalinas and the latin american orthodoxal marxism ones. It is highlighted that one aspect of the existing literal analysis about Cardoso s work is that the brazilian political studies have been underexplored, which take us to revisit this intellectual importance to the study of brazilian society formation.
Keywords: Ciência política; Intelectuais; Desenvolvimento econômico; Cardoso, Fernando Henrique, 1931; Estado - Modernização - Brasil; Desenvolvimento; Dependência; Pensamento politico brasileiro; Fernando Henrique Cardoso; Intelectuals; Development; Dependency; Brazilian Political Thought; CIENCIAS HUMANAS::CIENCIA POLITICA